Linking Agro‐Climatic Variability and Field Management to Wheat Yield in a Transition From Rainfed to Reservoir‐Fed Systems - Shahid Hameed Khan Khalil; Muhammad Shahzad Khattak; Ghani Akbar; Muhammad Ajmal (Irrigation and Drainage, 2026)
Climate change poses increasing risks to wheat production in semiarid regions. This study examined long‐term climate trends, wheat yield variability and farmers' perceptions and adaptation in District Rawalpindi, Pakistan. Wheat‐season (November–April) climate data (1989–2019) were analysed alongside a survey of 175 farmers. The results showed a significant increase in T min (0.05°C year −1 , p = 0.03), whereas T max increased slightly but nonsignificantly. Rainfall showed a declining, nonsignificant trend. Wheat yield exhibited high interannual variability with a weak increasing trend. Regression analysis identified rainfall as a significant predictor of yield ( β = 0.002, p = 0.011), explaining 46% of yield variation, with a 1% increase in rainfall increasing yield by 0.34%. Farmers' perceptions aligned with observed trends, with most reporting declining rainfall (78%) and increasing drought frequency (70%). Perception was significantly associated with education and farming experience. Adaptation practices included improved varieties, line sowing and minimum tillage, whereas the adoption of advanced technologies remained limited. Key barriers included knowledge gaps (86%), limited access to technology, financial constraints and weak institutional support. The findings highlight rainfall variability as the primary driver of yield instability and emphasize the need for strengthened advisory services, technology access and institutional support to enhance adaptive capacity.